The Book of Revelation and early Jewish textual culture - Allen, Garrick V. 1988- (Cambridge University Press, 2017)
The Book of Revelation and Early Jewish Textual Culture explores the relationship between the writing of Revelation and its early audience, especially its interaction with Jewish Scripture. It touches on several areas of scholarly inquiry in biblical studies, including modes of literary production, the use of allusions, practices of exegesis, and early engagements with the Book of Revelation. Garrick Allen brings the Book of Revelation into the broader context of early Jewish literature, including the Dead Sea Scrolls and other important works. Arguing that the author of the New Testament Apocalypse was a 'scribal expert, someone who was well-versed in the content of Jewish Scripture and its interpretation', he demonstrates that John was not only a seer and prophet, but also an erudite reader of scripture
Title from publisher's bibliographic system (viewed on 17 Jul 2017)
Keywords: Bible / Revelation / Criticism, interpretation, etc; Bible / Revelation / Criticism, interpretation, etc., Jewish; Bible / Revelation / Criticism, Textual; Bibel -- Sacharja; Bibel -- Offenbarung des Johannes; Bibel; Frühjudentum; Literatur; Intertextualität; Hochschulschrift